2015
DOI: 10.3906/tar-1411-36
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of microbial infections revealed by assessing nodulation infield-collected insects from Adana Province

Abstract: IntroductionEntomopathogenic microbes, occurring naturally, are virulent insect pathogens that include viruses, fungi, and bacteria. A wide range of lethal parasites also infect insects. Some of these organisms serve as important natural regulators of insect populations (Lacey et al., 2001). Appreciation of insect diseases and the possibilities of using insect disease agents in biocontrol programs have a long history (Steinhaus, 1957;Tanada, 1959). Commercially useful agents include viruses, fungi, bacteria, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 22 publications
1
12
0
3
Order By: Relevance
“…This is environment friendly because don't destroy beneficial insects. [8] b) Effect on seed germination and plant growth Many organic compounds effect the germination and growth of seed. 50 effects elongation of roots of linseed.…”
Section: Application In Agriculturementioning
confidence: 99%
“…This is environment friendly because don't destroy beneficial insects. [8] b) Effect on seed germination and plant growth Many organic compounds effect the germination and growth of seed. 50 effects elongation of roots of linseed.…”
Section: Application In Agriculturementioning
confidence: 99%
“…Therefore, insect defense mechanisms can limit the effectiveness of microbes deployed for biocontrol of insect. Now, we have also known that most insects in agrarian habitats of Kahramanmaraş and Adana/Turkey experience naturally occurring infections and the insects recover from invading microbes with fast-acting cellular defense actions, including nodule formation (Tunaz & Stanley, 2009;Tunaz et al, 2015). Their work also showed that insect cellular defense mechanism, nodulation, was affected by various factors including location, season, altitude, taxonomic position, and biological stage of insects collected.…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent reactions due to their atom economy, simplicity, high yields of products, and time‐saving features provide a simple and useful route for the synthesis of various heterocyclic compounds . Thiazolines show interesting biological activities with diverse applications in medicinal and agricultural chemistry , such as antimicrobial activity , melanin‐reducing activity (KHG22394 and whitening agent) , anti‐inflammatory properties , inhibition of p53‐mediated apoptosis and p53‐dependent gene transcription (pifithrin‐α) , and antifungal activity . Thus, the synthesis of these compounds is of significant interest to organic chemists.…”
Section: Introductionmentioning
confidence: 99%